2018
DOI: 10.1101/334821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Indexing Theory for Working Memory based on Fast Hebbian Plasticity

Abstract: Working memory (WM) is a key component of human memory and cognition. Computational models have been used to study the underlying neural mechanisms, but neglected the important role of short- and long-term memory interactions (STM, LTM) for WM. Here, we investigate these using a novel multi-area spiking neural network model of prefrontal cortex (PFC) and two parieto-temporal cortical areas based on macaque data. We propose a WM indexing theory that explains how PFC could associate, maintain and update multi-mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…This granularity imposes the channel burst length (BL) times the databus width (DQ) to be equal to 192 bits. The possible combinations of DQ and BL are (96, 2), (48, 4), (24,8), etc. Higher values of DQ width results in proportionally higher channel bandwidth, while adversely affecting the power dissipation and TSV area.…”
Section: Dimensioning Tsv Channel Width and Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…This granularity imposes the channel burst length (BL) times the databus width (DQ) to be equal to 192 bits. The possible combinations of DQ and BL are (96, 2), (48, 4), (24,8), etc. Higher values of DQ width results in proportionally higher channel bandwidth, while adversely affecting the power dissipation and TSV area.…”
Section: Dimensioning Tsv Channel Width and Frequencymentioning
confidence: 99%
“…In this paper, we have adopted the Bayesian Confidence Propagation Neural Network (BCPNN) as the candidate biologically plausible model. This model has, for a long time, been used for simulation of cortical associative memory processes, recently also of working memory, which is a key determinant of human intelligence and advanced cognitive function [7,8]. It has further been used to model sequence learning and serial recall [5], olfactory perception [6], and decision making in basal ganglia [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also features runtime-adaptable structural plasticity, which facilitates remapping of cortical components such as the connectivity of HCUs to maximize information entropy of the system, which can lead to better features [26]. BCPNN has recently been used for synaptic plasticity in large scale spiking cortex models of working memory function [9,10] and temporal sequence learning and generation, implemented on SpiNNaker [16]. BCPNN was further shown to reach 98.58% accuracy [25] on the famed MNIST [19] classification benchmark.…”
Section: Introductionmentioning
confidence: 99%
“…Meli and Lansner ( 2013 ) studied the neural interconnection scheme from a BCPNN model. Fiebig et al ( 2020 ) demonstrated how BCPNN could emulate the cortical working memory function. Recently, unsupervised hidden representation learning using BCPNN was benchmarked on MNIST.…”
Section: Introductionmentioning
confidence: 99%